The mulatta and the politics of race - Zackodnik, Teresa C. (Black women writers series., 2004)
From abolition through the years just before the civil rights struggle began, African American women recognized that a mixed-race woman made for a powerful and, at times, very useful figure in the battle for racial justice. The Mulatta and the Politics of Race traces many key instances in which black women have wielded the image of a racially mixed woman to assault the color line. In the oratory and fiction of black women from the late 1840s through the 1950s, Teresa C. Zackodnik finds the mulatta to be a metaphor of increasing potency. Before the Civil War white female abolitionists created th.